Credit coop sa Pampanga't Cebu - Aguilar, Mila D.; Institute for Filipino Cinema ([Quezon City] The Institute, 1990)
Presents two credit cooperatives, describing how they have alleviated the plight of their members.
VHS
Host, Ma. Ernie Selvido; editor, Mel L. Bacani III.
Keywords: Cooperative societies -- Philippines -- San Fernando (Pampanga); Cooperative societies -- Philippines -- Cebu; Sociology